The Efficacy of Raloxifene in the Treatment of Psoriasis: A Comprehensive Review - Ali, Thamer S.; Rasool, Abeer Mansour Abdel; Karmoosh, Ahmed Shuaib (International Journal of Innovative Research in Medical Science, 2024)
Psoriasis The skin gets thick and irritated when. The epidermis, the outermost layer of skin, proliferates excessively and is populated by dangerous T-cells. Certain medications, such as cyclosporine, retinoids, and methotrexate, may not always be safe, Raloxifene is drug that belong to a selective estrogen receptor modulator (SERM) that using in prevent and treat bone loss in postmenopausal women, Raloxifene is a therapeutic agent used to treat osteoporosis and psoriasis by targeting immune responses and cellular pathways involved in the disease process. to investigate the efficacy and mechanism of action of raloxifene in the management of psoriasis, with a focus on how it affects the generation of cytokines and the regulation of immune cells. The role of raloxifene in the management of psoriasis is still under debate, raloxifene may be effective in treating autoimmune diseases such as Psoriasis due to its function is the regulation of cytokine production and immune cells. Therefore, the ability of SERMs to act on both estrogen receptors and immune systems is instigating news in the field of drug development that the specific mechanisms underlying the association between Raloxifene and VDR ligand activity in psoriasis remain unclear and require further investigation. Future research exploring the cross-link between estrogen receptors, VDRs, and their respective ligands in psoriatic skin cells could provide valuable insights into the therapeutic potential of Raloxifene and other SERMs in the management of psoriasis.